Hubungan Riwayat Usia Penyapihan dengan Status Gizi Usia 24-36 Bulan - Jenie Palupi; Syiska Atik Maryanti (Puslitbang Sinergis Asa Professional, 2022)
Weaning age is the time when breastfeeding is stopped and replaced with complementary foods. Based on a preliminary study at the Posyandu Aster, Tegal Besar Village, Kaliwates District, Jember Regency, of the 10 respondents who had children aged 24-36 months who had weaned their children, only 2 were on time and the nutritional status of their children was good, and 8 people who did the weaning incorrectlytime. The purpose of this study was to determine the relationship between the history of weaning age and the nutritional status of children aged 24-36 months. Correlation analytic research design with cross sectional approach. The population is 128 mom who have children aged 24-36 months, the sample is 96. The technique used is simple random sampling with data collection using questionnaires, obtained =24 month weaning age as 28(29.16%), <24 months were 68 (70.84%). Nutritional status over 13 (13.54%), both were 26 (27, 08%), approximately as many as 42 (43.75%), poor as many as15 (15.62%). Statistically Based on Chi Square test and df = 1 and the 5% error level obtained x2 count is greater than x2 tables (9.12> 3.481) and KK forb 0,295. The conclusion is that there is a relationship between the history of weaning age and the nutritional status of children aged 24-36 months with a low/ weak but definite relationship strength. Health care workers should provide education on properweaning and weaning effects of improper weaning so that people do right on time.